2012
DOI: 10.1002/gepi.21707
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 60 Reported Glioma Risk SNPs Replicates Published GWAS Findings but Fails to Replicate Associations From Published Candidate‐Gene Studies

Abstract: Genomewide association studies (GWAS) and candidate-gene studies have implicated single-nucleotide polymorphisms (SNPs) in at least 45 different genes as putative glioma risk factors. Attempts to validate these associations have yielded variable results and few genetic risk factors have been consistently replicated. We conducted a case-control study of Caucasian glioma cases and controls from the University of California San Francisco (810 cases, 512 controls) and the Mayo Clinic (852 cases, 789 controls) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…27). A number of additional studies have replicated the association between rs78378222 and glioma risk (20, 32, 113, 114). …”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 92%
See 1 more Smart Citation
“…27). A number of additional studies have replicated the association between rs78378222 and glioma risk (20, 32, 113, 114). …”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 92%
“…Indeed, a recent study of 1,662 cases and 1,301 controls failed to replicate 52 variants previously implicated by candidate gene studies (20). In combination with more systematic approaches such as those making use of the exome array (21), these studies do not currently provide support for this class of susceptibility allele playing a major role in glioma predisposition.…”
Section: Introductionmentioning
confidence: 98%
“…The gene polymorphisms increased or decreased glioma sensibility by regulating the proliferation and apoptosis of cells (Das et al, 2013;Liang et al, 2013). (Das et al, 2013;Li et al, 2013b) (Shete et al, 2009;Wrensch et al, 2009;Jin et al, 2013;Li et al, 2013;Walcott et al, 2013;Walsh et al, 2013a;Walsh et al, 2013b). Several research groups have reported associations between the rs6010620 single nucleotide polymorphism (SNP) and glioma risk.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the published meta-analyses were based on the testing of multiple models (homozygote comparison, heterozygote comparison, recessive model, and dominant model), which are not independent so may increase the risk of false-positive results. Furthermore, some studies were not included in previous meta-analyses [20,21], including those published later with larger sample sizes and rigorous designs [22,23]. Considering that these factors could contribute to bias in the final results, we carried out an updated metaanalysis to provide a more reliable correlation between polymorphisms in IL-4/IL-13 pathway genes and glioma risk.…”
Section: Introductionmentioning
confidence: 97%